IMPLEMENTASI ALGORITMA FUZZY TSUKAMOTO DALAM MENGKLASIFIKASI TINGKAT RISIKO PENJUALAN HANDPHONE (Studi Kasus: Toko Handphone Bistion, Tembung) - Amanda Arba’a; Khairuddin Nasution; Tasliyah Haramaini (Jurnal Riset Multidisiplin Edukasi, 2026)
Bistion Mobile Store is a telecommunications retailer facing challenges in managing inventory and minimizing losses due to sales fluctuations. Inaccurate determination of sales risk levels often leads to stockpiling or shortages, which impact the store's financial stability. This study aims to develop an Android-based application capable of classifying sales risk levels automatically and accurately. The method used in this classification system is the Fuzzy Tsukamoto algorithm. The main variables used in the calculation process include sales volume, stock quantity, and market trends. In the Tsukamoto method, each consequence of an If-Then rule is represented by a fuzzy set with a monotonic membership function. The final result (output) is obtained using a weighted average. This system was developed on the Android platform to provide flexibility for Bistion Store owners to monitor sales risks anytime and anywhere. Test results show that the Fuzzy Tsukamoto algorithm is able to provide risk classification results (Low, Medium, High) that are in accordance with the store's historical sales data. The implementation of this application is expected to assist the management of the Bistion Mobile Phone Store in planning stock procurement and marketing strategies to minimize the risk of future losses.